Front crawl and backstroke sprint swimming have distinct differences along with similar patterns regarding trunk rotations - Nikodelis, T.; Gourgoulis, V.; Lola, A.; Ntampakis, I.; Kollias, I. (International Journal of Kinesiology & Sports Science, 2023)
Background: Front crawl and backstroke share similar trunk rotating characteristics and tempt coaches to transfer teaching parts from one stroke to the other intuitively. However, the degree of similarity has yet to be determined. The coordination of the pelvis and the 7th cervical vertebrae (C7), during yaw and roll rotation, when sprint swimming front crawl, and backstroke was studied. Methods: Thirty-four swimmers were assessed on their performance in25m-sprint of each stroke. Using inertial sensors, each segment`s time series of angular displacement was calculated. Their amplitudes, mean autocorrelation values, max cross-correlation coefficient, phase lag, and relative power at the main frequency were analyzed. For all comparisons, the p-value was set to <0.05. Results: Pelvis yaw and roll and C7 roll amplitudes were greater at backstroke, C7 yaw was greater at front crawl. Autocorrelations ranged from 0.79 to 0.82 except for the pelvis at front crawl in yaw which was 0.72±0.16. Relative power at the main frequency ranged from 47% to 52% except for the yaw pelvis` at the front crawl which was lower (32.81±14.09%). Backstroke had larger mean values in all cases and roll had larger mean values than yaw. Cross-correlation between the two segments yielded higher values at roll. At roll direction, the leading segment in the front crawl was the pelvis while in backstroke, it was the C7 which was true in all cases. In all cases, the coupling was slightly deviating from in-phase mode except from backstroke yaw which yield phase lag values of -13.35±1.14% of stroke cycle time. Conclusions: Although both strokes share similar characteristics their intersegmental coupling differs. The findings of the study imply that proper focus should be given to enhance only a positive transfer of learning between the two strokes.